PRÁTICAS DE EDUCAÇÃO MUSICAL EM INSTITUIÇÃO DE ACOLHIDA PARA ADOLESCENTES: POSSIBILIDADES E LIMITES - Roggenkamp, Carla Irene (2012)
This paper presents an analysis of the musical experiences developed by teenagers which find themselves at social and personal risk that are put under an institution’s care. The objective of this research was to investigate the relations between the teenagers and the classic, pop and mediatical emissions musical repertory, to reveal the contradictions inside the institution related to the functions granted to arts and music, also to verify in which measure the musical education techniques applied to this public can or not contribute to overcome this social reality. Were used as theoretical methodological references the Dialectical and Historic Materialism (MARX, ENGELS, 1999, 2008; MARX, 2006, 2008; MÉSZÁROS, 2002; CHAUÍ, 2007; KOSIK, 2010), authors that contributed with the bases for the State theories and that are related to the institution’s general aspects (GRUPPI, 1986; CARNOY, 1988; NETTO, 1992; PERONI, 2006; GRANEMANN, 2009; REZENDE, 2009; IAMAMOTO, 2010), and authors that write about the educational and aesthetics conceptions from critic perspective VÁZQUEZ, 1978; CANCLINI, 1984; FISCHER, 1987; PEIXOTO, 2003).The gathering and analysis of the data happened through the observation of the results achieved by the application of musical education techniques by the researcher, a music teacher, inside institution for a two years period. This paper assumes that musical education, and arts education in general, can and should contribute for a greater critical sense development among the attended population in order to lead to social transformation.